Peningkatan Pemahaman Ayah tentang Air Susu Ibu (ASI) Eksklusif sebagai Upaya Peningkatan Kepedulian Ayah terhadap ASI Eksklusif di Brimobda Bengkulu: Increasing Father's Understanding of Exclusive Breastfeeding as an Effort to Increase Father's Concern for Exclusive Breastfeeding at Brimobda Bengkulu - Bintang Agustina Pratiwi; Oktarianita Oktarianita; Andry Sartika (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
The results of a survey on fathers of under-five in Brimobda Bengkulu found that their children were not given exclusive breastfeeding. Fathers do not know what exclusive breastfeeding is, the benefits, and forms of father support that can support the success of exclusive breastfeeding. The service activity aimed to improve the understanding and skills of fathers in providing support for breastfeeding, especially exclusive breastfeeding through counseling activities and providing examples of the role of fathers in exclusive breastfeeding. The activity was carried out with the target of prospective fathers and fathers of under-five. The implementing team for this activity is a lecturer at the health sciences faculty of the University of Muhammadiyah Bengkulu. Community service that was carried out online using zoom media. This was due to the Covid-19 pandemic situation. Implementation was carried out in April 2021. Complete information about breastfeeding was given to fathers/husbands so that they understand what exclusive breastfeeding is, and provide support to breastfeeding mothers. The results of this activity indicated an increase in fathers' knowledge about breastfeeding and exclusive breastfeeding. Participants seemed enthusiastic in participating in this activity. It is advisable to continue to provide education about breastfeeding to groups of fathers and other prospective fathers. To be able to prepare to support breastfeeding. ABSTRAK Hasil survei pada ayah yang memiliki anak balita di Brimobda Bengkulu ditemukan bahwa anaknya tidak diberikan ASI Eksklusif. Ayah tidak mengetahui apa itu ASI Eksklusif, manfaatnya serta bentuk dukungan Ayah yang bagaimana dapat mendukung keberhasilan ASI Eksklusif. Kegiatan pengabdian bertujuan meningkatkan pemahaman dan keterampilan ayah dalam memberikan dukungan pemberian ASI khususnya ASI Eksklusif melalui kegiatan penyuluhan serta memberikan contoh bentuk peran ayah dalam pemberian ASI Eksklusif. Kegiatan dilakukan dengan sasaran calon ayah dan ayah yang mempunyai Balita. Tim pelaksana kegiatan ini adalah dosen fakultas ilmu kesehatan Universitas Muhammadiyah Bengkulu. Pengabdian kepada masyarakat yang dilakukan secara daring menggunakan media zoom. Hal ini dikarenakan situasi pandemi Covid-19. Pelaksanaan dilakukan pada bulan April. Informasi lengkap tentang ASI diberikan kepada para ayah/suami agar mereka memahami apa itu ASI eksklusif, serta memberikan dukungan kepada para ibu menyusui. Hasil dari kegiatan ini menunjukkan adanya peningkatan pengetahuan Ayah tentang ASI dan ASI Eksklusif. Peserta terlihat antusias mengikuti kegiatan ini. Sebaiknya edukasi tentang ASI terus dilakukan kepada kelompok ayah dan calon ayah lainnya. Agar bisa mempersiapkan diri untuk mendukung pemberian ASI.